2023
DOI: 10.3389/fonc.2023.1138284
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of platelet-to-albumin ratio as a clinical predictor for diffuse large B-cell lymphoma

Abstract: IntroductionDiffuse large B-cell lymphoma (DLBCL) is the most common subtypes of lymphoma. Clinical biomarkers are still required for DLBCL patients to identify high-risk patients. Therefore, we developed and validated the platelet-to-albumin (PTA) ratio as a predictor for DLBCL patients.MethodsA group of 749 patients was randomly divided into a training set (600 patients) and an internal validation set (149 cases). The independent cohort of 110 patients was enrolled from the other hospital as an external vali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Considering the effects of factors such as infection and chronic hepatic dysfunction on serum platelet counts and albumin levels, 30 the PAR, which combines both parameters, may offer reduced measurement variability and enhance reliability when compared to using either parameter alone. Wang et al studied the data of patients diagnosed with diffuse large B‐cell lymphoma and observed a U‐shaped relationship between the PAR and progression‐free survival; PARs greater than 8.6 or less than 2.7 were associated with shorter progression‐free survival 31 . Because platelets constitute an inflammatory biomarker, both decreased and increased platelet counts can reflect immune dysfunction and adverse survival, which can be attributed to the potential nonlinear association between the PAR and prognosis in patients with lymphoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the effects of factors such as infection and chronic hepatic dysfunction on serum platelet counts and albumin levels, 30 the PAR, which combines both parameters, may offer reduced measurement variability and enhance reliability when compared to using either parameter alone. Wang et al studied the data of patients diagnosed with diffuse large B‐cell lymphoma and observed a U‐shaped relationship between the PAR and progression‐free survival; PARs greater than 8.6 or less than 2.7 were associated with shorter progression‐free survival 31 . Because platelets constitute an inflammatory biomarker, both decreased and increased platelet counts can reflect immune dysfunction and adverse survival, which can be attributed to the potential nonlinear association between the PAR and prognosis in patients with lymphoma.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al studied the data of patients diagnosed with diffuse large B-cell lymphoma and observed a U-shaped relationship between the PAR and progression-free survival; PARs greater than 8.6 or less than 2.7 were associated with shorter progression-free survival. 31 Because platelets constitute an inflammatory biomarker, both decreased and increased platelet counts can reflect immune dysfunction and adverse survival, which can be attributed to the potential nonlinear association between the PAR and prognosis in patients with lymphoma.…”
Section: Discussionmentioning
confidence: 99%